2023
DOI: 10.3390/jcm12144584
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Index of Systemic Inflammation (AISI), Disease Severity, and Mortality in COVID-19: A Systematic Review and Meta-Analysis

Abstract: Combined indices of different haematological cell types appear to be particularly promising for investigating the link between systemic inflammation and coronavirus disease 2019 (COVID-19). We conducted a systematic review and meta-analysis to assess the aggregate index of systemic inflammation (AISI), an emerging index derived from neutrophil, monocyte, platelet, and lymphocyte counts, in hospitalized COVID-19 patients with different disease severity and survival status. We searched electronic databases betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As for AISI, in patients with COVID-19, increased values upon admission predict severe or fatal evolution [47]; therefore, determining the AISI value upon admission can help triage the patients with a bad prognosis [48]. In patients with hemophagocytic lymphohistiocytosis, the aggregate index of systemic inflammation (AISI) was also an independent risk factor for 28-day mortality [49].…”
Section: Discussionmentioning
confidence: 99%
“…As for AISI, in patients with COVID-19, increased values upon admission predict severe or fatal evolution [47]; therefore, determining the AISI value upon admission can help triage the patients with a bad prognosis [48]. In patients with hemophagocytic lymphohistiocytosis, the aggregate index of systemic inflammation (AISI) was also an independent risk factor for 28-day mortality [49].…”
Section: Discussionmentioning
confidence: 99%
“…As for AISI, in patients with COVID-19, increased values upon admission predict severe or fatal evolution [35]; therefore, determining the AISI value upon admission can help triage the patients with a bad prognosis [36]. In with hemophagocytic lymphohistiocytosis, the aggregate index of systemic inflammation (AISI) was also an independent risk factor for 28-day mortality [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel blood inflammatory indexes (hereafter BIIXs) based on the correlation among blood count parameters, such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune inflammatory index (SII), system inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI), have been investigated in almost all fields of clinical research and reported as reliable in quantifying inflammation, the status of systemic illness, and the prognosis [10][11][12][13][14][15][16][17][18]. Hypothyroidism is a well-known inflammatory and oxidative trigger.…”
Section: Introductionmentioning
confidence: 99%